Established and Emerging Treatments of Skin GvHD - Link-Rachner, Cornelia S.; Sockel, Katja; Schuetz, Catharina (Frontiers in Immunology, 2022)
Graft-versus-host disease is a severe allo-immune reaction and complication following allogeneic stem cell transplantation causing significant post-transplant morbidity and mortality. Pathomechanisms of acute GvHD (aGvHD) are much better understood than those leading to chronic GvHD (cGvHD) with its pleiomorphic presentations. Nevertheless aGvHD may be difficult to control especially when developing into cGvHD. There is an urgent need both for predictive biomarkers for cGvHD and better understanding of inflammatory pathways which may be targeted by small molecules or cell based therapies. The authors present both established as well as emerging treatment approaches with focus on GvHD of the skin.